Borobudur Temple Area: Second Restoration Towards A Tourist Destination 1973 – 1983 - Talitha Aisyatul Chasanah; Shokheh, Mukhammad; Rudi, Rudi (Journal of Indonesian History, 2024)
The results of this research show that, in 1973 – 1983, the restoration of Borobudur Temple was carried out which involved the process of cleaning rocks, dismantling and reassembling rocks. This restoration project is important for preserving Indonesia's cultural heritage and increasing tourism. The second restoration of Borobudur Temple in 1983 had a major impact on the socio-economic life of the surrounding community. Physical and non-physical changes occur, including land conversion, changes in the social order, and improvements in infrastructure and new job opportunities. The research method used for this research is historical research methods, namely heuristics, source criticism, interpretation, and historiography. The results of this research show that the restoration of Borobudur Temple II has had a positive impact on changes in the social and economic order of the surrounding community. The construction of the Borobudur Temple Tourist Park has increased tourist visits and provided economic benefits for the local community. Although there is some controversy regarding the relocation of residents and the relocation of markets, this increase in tourism provides additional employment opportunities and improves the family economy. The establishment of the Borobudur Temple Tourist Park provides economic, educational, environmental and welfare benefits for the surrounding community, but it is necessary to improve environmental management, economic development and education to optimize the benefits of Borobudur Temple for the community.